Trielectrolyte aluminum-air cell with high stability and voltage beyond 2.2 V. (August 2020) - Wang, L.; Cheng, R.; Liu, C.; Ma, M.C.; Wang, W.; Yang, G.; Leung, M.K.H.; Liu, F.; Feng, S.P.
Abstract: The aluminum-air battery with remarkably high theoretical energy density is a promising candidate for the increasingly diverse applications in modern society. However, the self-corrosion of Al is one great challenge and limits the practical operating voltage around 1.2–1.6 V. Here, a trielectrolyte aluminum-air cell (TEAAC) is first developed to integrate polymer ion-exchange membranes, organic electrolyte, alkaline anolyte, and acidic catholyte, reaching an open-circuit voltage of 2.2 V, which is among the highest reported values for Al-air cells. The adoption of organic alkaline anolytes maintains fairly good electrochemical activity of aluminum while significantly suppressing the self-corrosion reaction. The acid-base neutralization is avoided with proper arrangement of two ion-selective membranes. The TEAAC demonstrates stable and robust performance through long-time discharge tests and shows good mechanical rechargeability. The new cell design also allows usage of low-cost commercial-grade aluminum. This work provides an alternative route for cost-effective and reliable Al-air battery systems. Graphical abstract: Image 1 Highlights: The trielectrolyte Al-air cell (TEAAC) was first developed with superior high stability and voltage. The organic anolyte was adopted to strategically suppress the parasitic self-corrosion reaction. The acidic catholyte enables a high potential of oxygen reduction reaction, boosting up the voltage. Ion-exchange membranes and the bridge electrolyte avoid the neutralization reaction. Low-cost kitchen aluminum foil can be used as the replaceable anode in this work.